Tendon reflex is suppressed during whole-body vibration. (October 2016) - Karacan, Ilhan; Cidem, Muharrem; Yilmaz, Gizem; Sebik, Oguz; Cakar, Halil Ibrahim; Türker, Kemal Sıtkı
Abstract: In this study we have investigated the effect of whole body vibration (WBV) on the tendon reflex (T-reflex) amplitude. Fifteen young adult healthy volunteer males were included in this study. Records of surface EMG of the right soleus muscle and accelerometer taped onto the right Achilles tendon were obtained while participant stood upright with the knees in extension, on the vibration platform. Tendon reflex was elicited before and during WBV. Subjects completed a set of WBV. Each WBV set consisted of six vibration sessions using different frequencies (25, 30, 35, 40, 45, 50 Hz) applied randomly. In each WBV session the Achilles tendon was tapped five times with a custom-made reflex hammer. The mean peak-to-peak (PP) amplitude of T-reflex was 1139.11 ± 498.99 µV before vibration. It decreased significantly during WBV (p < 0.0001). The maximum PP amplitude of T-reflex was 1333 ± 515 μV before vibration. It decreased significantly during WBV (p < 0.0001). No significant differences were obtained in the mean acceleration values of Achilles tendon with tapping between before and during vibration sessions. This study showed that T-reflex is suppressed during WBV. T-reflex suppression indicates that the spindle primary afferents must have been pre-synaptically inhibited during WBV similar to the findings in high frequency tendon vibration studies.